Horizontal mergers with synergies: first-price vs. profit-share auction - Wei Ding; Cuihong Fan; Elmar G. Wolfstetter (Sonderforschungsbereich/Transregio 15 - Governance and the Efficiency of Economic Systems (GESY), 2010)
We consider takeover bidding in a Cournot oligopoly when firms have private information concerning the synergy effect of merging with a takeover target. Two auction rules are considered: standard first-price and profit-share auctions, supplemented by entry fees. Since non-merged firms benefit from a merger if the synergies are low, bidders are subject to a positive externality. Nevertheless, pooling does not occur; and the profit-share auction is strictly more profitable than the first-price auction, regardless of whether firms observe the synergy parameter or only the winning bid before they play the oligopoly game.
urn:nbn:de:bvb:19-epub-13218-0
Keywords: G34; D44; H23; L13; D43; 330; Horizontal mergers; takeovers; auctions; externalities; oligopoly; Übernahme; Auktionstheorie; Synergie; Asymmetrische Information; Oligopol; Spieltheorie; Theorie